2022
DOI: 10.3389/fpubh.2022.799731
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Aspects to Precise Health Strategies in Native Hawaiian and Other Pacific Islanders Using Statins

Abstract: Cardiometabolic disorders (CD), including cardiovascular disease (CVD), diabetes, and obesity, are the leading cause of health concern in the United States (U.S.), disproportionately affecting indigenous populations such a Native Hawaiian and Other Pacific Islanders (NHOPI). Dyslipidemia, a prevalent risk factor for the development and progression of CVD, is more prone to occur in NHOPI than other populations in the U.S. High-intensity statin therapy to reduce low-density lipoprotein cholesterol is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Historically, NHOPI individuals have received relatively less attention in cardiovascular health research. 1 In addition, within the NHOPI racial category, ethnic groups such as Hawaiian, Samoan, Tahitian, and Māori individuals are seldom delineated and thereby understudied. To explore this unmet need further, we systematically reviewed existing human health data sets and large-scale epidemiological cohort studies across different biological databases and biobanks covering various cardiovascular disease phenotypes to assess current NHOPI representation therein ( Table 1 ).…”
Section: The Nhopi Data Disparity and Consequences Of Demographic Agg...mentioning
confidence: 99%
See 4 more Smart Citations
“…Historically, NHOPI individuals have received relatively less attention in cardiovascular health research. 1 In addition, within the NHOPI racial category, ethnic groups such as Hawaiian, Samoan, Tahitian, and Māori individuals are seldom delineated and thereby understudied. To explore this unmet need further, we systematically reviewed existing human health data sets and large-scale epidemiological cohort studies across different biological databases and biobanks covering various cardiovascular disease phenotypes to assess current NHOPI representation therein ( Table 1 ).…”
Section: The Nhopi Data Disparity and Consequences Of Demographic Agg...mentioning
confidence: 99%
“…As a result of multiple risk factors, NHOPI individuals are disproportionately burdened by cardiometabolic diseases. 1 , 3 Recent studies have shown that NHOPI patients have high rates of undiagnosed T2D as well as high rates of diagnosed metabolic disease: 19% to 22% for T2D, and 16% to 35% for impaired glucose tolerance. 1 , 2 One recent prospective study found a prevalence of T2D as high as 57.9%, noting that many cases were previously undiagnosed.…”
Section: Health Disparities In Nhopi Cardiometabolic Disease Burdenmentioning
confidence: 99%
See 3 more Smart Citations